Analysis of the Suitability of Teaching Modules with the Implementation of Biology Learning on Ecosystem Material in Grade X of State Senior High School in Medan City for the 2024/2025 Academic Year - Sitanggang, Lawren; Sipahutar, Herbert (Journal of Biology Education, 2025)
This study aims to determine the suitability between planning (teaching modules) and the implementation of biology learning on ecosystem material in class X SMAN in Medan. The research population was Biology teachers and students in class X of public high schools in Medan City that are accredited A and have implemented the Merdeka Curriculum. Samples of Biology teachers (7 people) and students (252 people) were taken purposively from SMAN 1, SMAN 5 and SMAN 12 Medan.  Lesson planning data were collected through document analysis of teaching modules while learning data were collected using classroom observation techniques and questionnaires given to students. These data were confirmed and corroborated through teacher interviews. The results showed that the ability of Biology teachers in class X in public high schools in Medan City in developing teaching modules was classified as very good with an average value of 89,10 ± 20,55, while the ability to implement learning based on teaching modules was classified as a good category with an average value of 85,49 ± 5,92. The implementation of learning in the classroom has been by what was planned in the module, although some aspects such as the delivery of learning benefits, application of the model, reflection, evaluation, and, attachment have not been optimal. Both planning and implementation of learning are by the Process Standards in Permendikbud No. 16 of 2022.